2017
DOI: 10.1371/journal.pone.0180476
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activities of polysaccharides separated from Inonotus obliquus via the modulation of oxidative stress in mice with streptozotocin-induced diabetes

Abstract: This study evaluated the effects of Inonotus obliquus polysaccharides (IOs) on diabetes and other underlying mechanisms related to inflammatory factors and oxidative stress in a mouse model of streptozotocin (STZ)-induced diabetes. Four weeks administration of metformin (120 mg/kg) and IO1-4 (50%-80% alcohol precipitation), or IO5 (total 80% alcohol precipitation) at doses of 50 mg/kg reverses the abnormal changes of bodyweights and fasting blood glucose levels of diabetic mice. IOs significantly increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 57 publications
1
40
2
Order By: Relevance
“…The dry matter extracts obtained from culture broth of I. obliquus were found to improve serum insulin levels, moderately expand the pancreatic islets, and reduce pancreatic injuries in alloxan‐induced diabetic mice (Sun et al, ). It was found that I. obliquus also enhanced the serum levels of insulin and alleviated the metabolic derangement of glucose enzymes in STZ‐induced diabetic mice (Wang et al, ). Similarly, polysaccharide extract obtained from I. obliquus was reported to exert a hypoglycemic effect by inhibiting the action of α‐glucosidase, which resulted in a delayed glucose absorption in the digestive organs following meals (Chen, Lu, Qu, Wang, & Zhang, ).…”
Section: Influence Of I Obliquus Extracts On Serum Glucose Insulin mentioning
confidence: 99%
“…The dry matter extracts obtained from culture broth of I. obliquus were found to improve serum insulin levels, moderately expand the pancreatic islets, and reduce pancreatic injuries in alloxan‐induced diabetic mice (Sun et al, ). It was found that I. obliquus also enhanced the serum levels of insulin and alleviated the metabolic derangement of glucose enzymes in STZ‐induced diabetic mice (Wang et al, ). Similarly, polysaccharide extract obtained from I. obliquus was reported to exert a hypoglycemic effect by inhibiting the action of α‐glucosidase, which resulted in a delayed glucose absorption in the digestive organs following meals (Chen, Lu, Qu, Wang, & Zhang, ).…”
Section: Influence Of I Obliquus Extracts On Serum Glucose Insulin mentioning
confidence: 99%
“…In this study, we found that hot water extracted-Chaga polysaccharides significantly mitigated genotoxicity by enhancing the expression of DNA repair genes in UVB-induced zebrafish embryos. The major polysaccharide found in Chaga mushroom was β-glucan, a polymer of β-D glucose, which is documented to possess several health benefits [18]. β-glucan has been reported to have anti-diabetic, anti-proliferative properties, and anti-tumorigenic properties [19].…”
Section: Discussionmentioning
confidence: 99%
“…UV-induced zebrafish models have also been developed to study the expression of DNA repair genes and tumor suppressor genes regulation [1517]. Furthermore, transparent zebrafish casper mutants have been consistently used for tumour-related and toxicological studies for assessing the phenotypic manifestations during development [18]. Such avenues will be worthy to explore the specific DNA repair genes that might play additional roles in embryological development.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritionally, these interactions may also play an important role in the digestive tract of humans, regarding the metabolism of both anthocyanins and polysaccharides [ 142 , 147 ]. Recently, the antidiabetic activity of polysaccharides has also been reported [ 148 , 149 , 150 ]. These effects were mostly attributed to enzyme inhibition related to starch digestion and mechanisms related to inflammatory factors and oxidative stress, exerting favorable effects on glucose homeostasis and reducing insulin resistance.…”
Section: Why Anthocyanins?mentioning
confidence: 99%